The Impact of Board Gender Diversity on Firm Financial Performance: Evidence from FTSE 100 Firms in the UK - CHAI, YUEXIN (2020)
This research explores the impacts of the board gender diversity on firm financial performance, which has been heatedly debated in academia. This study not only finds out the impact of board gender diversity on the firm financial performance, but also explores whether the firm has female directors because of tokenism through empirical analysis. The research sample is the UK FTSE 100 listed firms from 2015 to 2019. After the 2011 Davis Report issued ten recommendations for advocating gender diversity on the board, the percentage of females on the board of UK firms has increased significantly. Therefore, it is of great significance to explore the impact of board gender diversity on the firm financial performance and to appoint female directors as tokens. After the Ordinary Least Squares (OLS) regression of the research samples, this study found that the gender diversity of the board of directors has no significant positive effects on the firm's return on assets. Moreover, one female director or two female directors will bring about a significant increase in return on assets, so this study did not find the tokenism of UK firms.